MODEL PENGELOLAAN CAGAR ALAM TELUK ADANG DALAM UPAYA KONSERVASI SUMBERDAYA LINGKUNGAN DI KABUPATEN PASER KALIMANTAN TIMUR - Firman Firman; Akhmad Rizali; Fakhrur Razie; Taufik Hidayat (EnviroScienteae, 2017)
This study aims to analyze Resources potentials (R), Organizations (O) and Norm (N) conservation center of Adang Bay nature reserve and village conservations area and formulate management model of Adang Bay nature reserve in the effort of conservation of environmental resources in Paser Regency of East Kalimantan.    The research was conducted in eight villages with in Adang Bay reserve area (Padang Pangrapat village, Pondong Baru village, Pasir Mayang village, Muara Adang village, Air Mati village, Teluk Waru village, Muara Telake village, and Petiku village) the study was conducted in May to September 2016. The analysis used was qualitative descriptive with data collection methods by triangulation in – depth interview, observation, and FGD, researchers information were selected by the purposive method.    The result of this research is to know the potential of resources contained in Adang Bay Nature reserve area of 18.956 Ha of mangrove area, community resources that live in the area as many as 14.767 people and Adang bay areas are very suitable for aquaculture of fish pond and shrimp, and the high spirit of community mutual corporation in eight conservation village, the Adang Bay Nature Reserve consist of eight definitive villages so that 30 % empowerment budget is available, as well as BUMDes that can be collaborated as a conservation village promotion effort.    Adang Bay Nature Reserve Management Model that supports is Collaborative Management Model, with this model the existence of Adang Bay Reserve does not change the status of the area. The management program stages are directed to protection, preservasion, and utilization with consideration of social, economy and ecology in Adang Bay area.